A hyperbranched β-d-glucan with compact coil conformation from Lignosus rhinocerotis sclerotia. (15th June 2017) - Hu, Ting; Huang, Qilin; Wong, Kahing; Yang, Hong; Gan, Jingsi; Li, Yanru
Highlights: LRP was extracted from the sclerotia of Lignosus rhinocerotis with 0.5 M NaOH. LRP was a (1 → 3)-β-glucan backbone bearing a hyperbranched side chain linked at O6. The hyperbranched side chain had two (1 → 3, 6)-β- and three (1 → )-β-glucose residues. Mw, < S 2 > z 1/2, Rh and [ η ] of LRP were 2.88 × 10 5  g/mol, 30.36 nm, 22.34 nm and 131.50 ml/g. Based on α, β, df and ρ, LRP (DB = 0.76) adopted compact coil conformation in LiCl/DMSO. Abstract: An alkali-soluble polysaccharide was extracted from Lignosus rhinocerotis sclerotia (LRP). Its structural characteristics were determined by GC–MS, FT-IR, GC, 1D and 2D NMR combined with Smith degradation and methylation analysis. The LRP had a (1 → 3)-β-d -Glcp backbone with every three residues bearing a (1 → 6)-linked and hyperbranched side chain that contained three (1 → 6)-β-d -Glcp residues as secondary main chain and two terminal β-d -Glcp residues linked at O3. The degree of branching was 0.76 from GC–MS analysis, implying a highly branched structure for LRP. The Mw, < S 2 > z 1/2, Rh and [ η ] values of LRP in 0.25 M LiCl/DMSO were measured by SEC-MALLS-Vis-RI combination technology to be 2.88 × 10 5  g/mol, 30.36 nm, 22.34 nm and 131.50 ml/g, respectively. Furthermore, the exponent α of [ η ] –Mw, β of < S 2 > z 1/2 –Mw, the fractal dimension df and molecular parameter ρ were determined to be 0.20, 0.33, 2.50 and 1.36, demonstrating that the LRP was a hyperbranched polysaccharide and adopted a compact coil conformation in LiCl/DMSO.